Involvement of gamma interferon inducible lysosomal thiol reductase in the innate immune responses of red swamp crayfish, Procambarus clarkii. (October 2019) - Liu, Min; Liu, Li; Abbas, Muhammad Nadeem; Kausar, Saima; Zhang, Jun-Wei; Ye, Zhi-Ze; Qian, Xing-Yi; Zhao, Xiao-Ming; Chu, Sheng-Hui; Dai, Li-Shang
Abstract: The Gamma interferon inducible lysosomal thiol reductase (GILT) plays a key biological role in the immune responses and involves in the processing of class II MHC-restricted antigen by stimulating disulfide bond reduction in mammals. To determine the biological function of GILT in the innate immune system of crustaceans, we sequenced and cloned GILT gene from red swamp crayfish, Procambarus clarkii ( Pc-GILT ). The deduced amino acid sequence of Pc-GILT contained the putative conserved structures of the GILT family proteins: the GILT signature (CQHGX2ECX2NX4C) sequence and the active site (CXXS) motif. Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and Western blot analysis suggested that a recombinant Pc-GILT protein was successfully expressed in Escherichia coli ( E. coli ). Quantitative real-time PCR analysis showed that Pc-GILT transcript level was highest in the hepatopancreas followed by the gut, heart and muscles. Additionally, we analyzed the transcription level of Pc-GILT gene in hepatopancreas of red swamp crayfish under biotic stress conditions. The expression of Pc-GILT gene upregulated after viral (poly I:C) and bacterial (peptidoglycan, lipopolysaccharide) infection. The suppression of Pc-GILT by double stranded RNA influenced the transcript levels of various immune-related genes. These observations indicate that the Pc-GILT probably plays a key biological role in the innate immune responses of red swamp crayfish, since it modulates the expression of genes associated with immune pathways. Highlights: A Gamma interferon inducible thiol reductase from Procambarus clarkii ( Pc-GILT ) was identified for the first time. A rabbit anti-Pc-GILT polyclonal antibody was prepared. The expression patterns of GILT under immune challenges were investigated. GILT RNAi influenced the expression of immune-related genes.